Livro de Autor - Jorge, Sofia Matalonga Barreiros (2015)
It is ower intention to share the experience of a work unit whose purpose was the development of a with 9th graders in the discipline of visual education that targeted the development of twenty-six books with matchbox format. The work done with students sought to approximate the emotional and personal reaction of the student to a deeper knowledge and a better understanding of art, where the construction of the book should express the identity of the student, influencing a narrative and its graphic design